2013
DOI: 10.1161/circresaha.112.266882
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Associated Matrix Proteolysis and Heart Failure

Abstract: The extracellular matrix (ECM) is a complex entity containing a large portfolio of structural proteins, signaling molecules, and proteases. Changes in the overall integrity and activational state of these ECM constituents can contribute to tissue structure and function, which is certainly true of the myocardium. Changes in the expression patterns and activational states of a family of ECM proteolytic enzymes, the matrix metalloproteinases (MMPs), have been identified in all forms of LV remodeling and can be a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
139
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(144 citation statements)
references
References 161 publications
(436 reference statements)
2
139
1
2
Order By: Relevance
“…19) In the infarcted myocardia, due to injury to the cardiomyocyte membrane, more glutamic oxaloacetic transaminase (GOT) will be released into the serum, prohibiting the transamination from glutamate to α-ketoglutaric acid in myocardia and leading to the increase of glutamate in infarcted myocardia. In addition, necrotic cardiomyocyte means more proteins are decomposed, 20) which may also contribute to the increased level of glutamate in the infarcted myocardia. Previous studies showed that a higher level of glutamate was correlated with ongoing myocardial ischemia and that it could activate the generation of NO, inducing the production of free radicals and leading to cardiomyocyte death by mediating inflammatory and cytotoxic actions.…”
Section: Metabolic Characteristics Of MImentioning
confidence: 99%
“…19) In the infarcted myocardia, due to injury to the cardiomyocyte membrane, more glutamic oxaloacetic transaminase (GOT) will be released into the serum, prohibiting the transamination from glutamate to α-ketoglutaric acid in myocardia and leading to the increase of glutamate in infarcted myocardia. In addition, necrotic cardiomyocyte means more proteins are decomposed, 20) which may also contribute to the increased level of glutamate in the infarcted myocardia. Previous studies showed that a higher level of glutamate was correlated with ongoing myocardial ischemia and that it could activate the generation of NO, inducing the production of free radicals and leading to cardiomyocyte death by mediating inflammatory and cytotoxic actions.…”
Section: Metabolic Characteristics Of MImentioning
confidence: 99%
“…Many types of matrix metalloproteinases are regarded as particularly being related with myocardial remodeling (8,16). For that reason, matrix metalloproteinase inhibitors have been suggested as a potential therapeutic approach in the prevention of cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In the pathological conditions with unbalanced matrix metalloproteinases activities, changes in tissue inhibitors of matrix metalloproteinases levels are considered important. The pathological effects of matrix metalloproteinases and tissue inhibitors of matrix metalloproteinases in cardiovascular disease processes that involve vascular remodeling, atherosclerotic plaque instability, and left ventricular remodeling after myocardial infarction are of considerable interest (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…This finding is noteworthy, since the changes in ECM structure and function directly contribute to the adverse myocardial remodeling in HF of various etiology. 6 …”
Section: Discussionmentioning
confidence: 99%